Factors That Influence the Quality of Local Government Financial Reports (Case Study on Jambi City Regional Apparatus Organizations) - Arief Isdayanto; Enggar Diah Puspa Arum; Reni Yustien; Fitrini Mansur (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to test or analyze whether Human Resource Competency, Internal Control System, Use of Information Technology, Internal Audit, and Implementation of Government Policy influence the Quality of Jambi City Regional Government Financial Reports. The data used is primary data obtained through administering questionnaires to the Financial Administration Officials of Regional Apparatus Organizations (PPK-OPD) and the Finance Section of the Regional Financial and Asset Management Agency (BPKAD) in the Jambi City Regional Government. The sampling technique used the saturated sample method with a sample size of 48 respondents. The data analysis method uses descriptive analysis and Structural Equation Modeling (SEM) - Partial Least Square (PLS) analysis using Microsoft Excel and SmartPLS software.lThe research results show thatlHuman Resource Competency, InternallControl Systems, and Implementation ofmGovernment Policies influence thenQuality of RegionalnGovernment FinancialmReports. Meanwhile, themuse of InformationnTechnology and Internal Audit has no effectlon thelQuality oflRegional Government FinanciallReports